Study on anatomical variations of nose and paranasal sinuses in patients with sinonasal polyposis - Shrestha, Akriti; Kattel, Kolaj; Rana, Sabi; Devkota, Sagar; Shrestha, Astika; Piya, Pronin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Knowledge regarding the sinonasal variations plays an important role in the management of sinonasal diseases. Despite being postulated as one of the risk factors for sinonasal diseases, its role in the pathogenesis of nasal polyp is still unclear. This study was done to determine the prevalence of sinonasal anatomical variations by CT imaging and examine its association with sinonasal polyposis (SNP). Method: A descriptive cross-sectional study was conducted from January, 2019 to January, 2020 at a tertiary care center after receiving ethical approval from the institutional review committee of the hospital. Patients above 17 years of age having sinonasal polyp and not responding to 3-4 weeks of medical treatment were included in the study. Convenience sampling was done. Data were collected and entered in Microsoft excel and analyzed using statistical package for the social sciences version 24.0. Results: Among 72 patients, 86.11% of the patients were found to have anatomical variations of nose and paranasal sinuses with Agger nasi (79.09%) and deviated nasal septum (DNS) (72.5%) being the most common variations noted, 29% of patients were found to have a single variation while multiple variations were seen 70.9% of patients. Conclusions: Our study showed that patients with sinonasal polyps have a higher prevalence of sinonasal anatomical variations and severity of polyp increased with the presence of more than one variation in a patient.